Direct and Indirect Effects of Fluorine on the Photocatalytic Performance of Titania-Based Photocatalysts - Wu, Siming; Schmuki, Patrik (Energy Technology, 2023)
TiO2 used as a light-absorbing semiconductor represents the classic benchmark for photocatalytic solar energy conversion and many other photocatalytic reactions. Various strategies are developed to improve the photoresponse of TiO2-based materials, such as bandgap engineering or surface sensitization in combination with nanostructuring and geometry optimization. The present feature article is focused on direct and indirect approaches involving bulk or surface fluorine used to tune the surface chemistry, electronic structure, and the morphology of TiO2 photocatalysts. A comprehensive overview is provided on fluorine effects on TiO2, involving morphology modifications, and how surface or bulk fluorine affect the photocatalytic performance of TiO2. After outlining some basic interaction principles of F and TiO2, characterization techniques for different fluorine species are discussed. It is reviewed how fluorine during crystal growth mediates the morphology of TiO2; then how surface fluorination and doping fluorine effects can be beneficially utilized in photocatalysis are discussed. Finally, synergistic effects between fluorine and cocatalyst are discussed, for example, the use of lattice fluorine species to stabilize Pt single-atom cocatalysts. Finally, the challenges and outlook on further advancing the development of fluorine effects are highlighted.
CRIS-Team Scopus Importer:2023-05-05
Keywords: lattice fluorine doping; photocatalysis; surface fluorination; titanium oxide